Effect of acethylcholine on in vitro contractility of seminal vesicles - Orhan, Irfan; Onur, Rahmi; Ayar, Ahmet; Taşdemir, Cemal (My University, 2004)
Introduction: Seminal vesicles play important roles in male fertility by both their secretions and contractile characteristics. With the intense muscle mass in their wall and contractile features of these muscles, they are not only involved in fertility but also in ejaculation period. Since involved in ejaculation, regulations of tonus of this muscle will erve a new approach to the premature ejaculation that is among to the most common male sexual dysfunction. Determination of involvement of purinergic system in the innervation of these vesicles which is known to have sympathetic as well as parasympathetic innervations has lead to the investigation of mechanisms involved in the regulation of this organ. In the present experimental study, it was aimed to determine the effects of acethylcholine (ACh) on the contractility of isolated seminal vesicle. Materials and Methods: Seminal vesicle strips used in this study were isolated from 200-250 g male Wistar rats. Following decapitation, the lower abdomen was opened and seminal vesicles were removed and about 0.5 × 0.2 cm strips were obtained. The strips were placed in were placed in a jacketed organ bath containing Krebs' solution at 37°C and pH 7.4, constantly gassed with 95% O2-5% C02 and after equilibration under one gram of resting tension isometric contractions were recorded. After equilibration under 1 gram of resting tension, a 10-minute control recording was performed from strips those developed spontaneous contractions. At the end of this period ACh (10 ?M) was applied to the organ bath to induce contractions and then atropine was applied to determine its effect on these ACh-induced contractions. Amplitude (mg) and frequency (number of contractions/10-min) of contractions and area under the contraction curves were evaluated by 10-minute intervals. Results: Spontaneous contractions, even small, were developed in strips studied during the equilibration period. Maximal contractile response to the acethylcholine 10-9, 10-6 and 10-5 M were recorded. The mean maximal contractile response to ACh (10-9, 10-6 and 10-5 M) were 0.7±1.4 mg, 985±145 mg and 1189±156 mg, respectively. Atropine was inhibited the A Ch-induced contractile responses by an immediately started effect. Atropine (1 micro molar) inhibited the area under the contractile curve induced by 10-5 M ACh by 85%; which was reached to a complete inhibition within 220±35 s of atropine application. Conclusion: In rat seminal vesicle ACh causes contractions, which are, can be inhibited by atropine. Investigation of the effects of variety of specific agents on these contractions is of interest with respect to the development of therapy for male infertility and premature ejaculation.
Ase?ilkol? i? in ? in v? itro ve? iküla se?inal?is kontrak? iyonlarina etk? i?i
Keywords: Acethylcholine; Contractility; Seminal vesicle